The Role of Basic Social and Cultural Sciences (ISBD) in the Development of the Nation's National Development - Istikomah, Istikomah; Hikam, Is Maelal; Ridwan, Ridwan (Jurnal Multidisiplin Indonesia, 2025)
Indonesia is known as a country rich in diverse cultures, from Sabang to Merauke, so rich in hundreds of ethnic groups with languages, customs, and traditions that vary in every part of the archipelago. This is a characteristic or characteristic of the Indonesian nation, which also has an important role and function for the development of the national development of the Indonesian nation. In this study, the library method is used, where in the process of compiling it by collecting various references from books, magazines, and also research from previous journals. A very significant role in the development and development of national culture. Through Higher Education, in addition to the importance of teaching, cultural sciences can perform their role optimally in development. Starting from the element of community service, cultural scientists can carry out their practical role through "service" and community empowerment activities.